The politics of leadership : superintendents and school boards in changing times - Petersen, George J.; Fusarelli, Lance D. 1966- (Emerald Publishing Limited : IAP, 2005)
The primary contribution of this book, is not its advocacy of a specific position but rather, its objective analysis of cogent topics. The content prompts us to consider governance in relation to quality education and to ponder alternative policy strategies that have yet to be fully evaluated. As a young doctoral student more than a few years ago, William Van Til, an eminent scholar and a mentor, reminded me almost daily that members of the education profession had a moral responsibility to address the most difficult questions about education and democracy. These enduring queries, he argued, extended to determining how this critical social service should be organized and controlled and to determining the appropriate roles for administrators and teachers. Those in our profession who fail to heed his advice by remaining indifferent to these philosophical dilemmas should consider Plato's long-standing warning: "One of the penalties for refusing to participate in politics is that you end up being governed by your inferiors."
Keywords: School superintendents -- United States.; School boards -- United States.; Educational leadership -- Political aspects -- United States.; Education -- Administration -- School Superintendents & Principals.; Educational administration and organization.; elektronické knihy; electronic books